Role of Work Activities and Knowledge Sharing in Employee Sustainable Social Well-Being Along with the Moderating Role of Supply Chain Education - Restu, R.; Hayat, Atma; Baharuddin, Baharuddin; Fibriasari, Hesti (International Journal of Supply Chain Management, 2020)
The objective of this study is to examine the role of work activities and knowledge sharing in employee sustainable social well-being. The moderating role of supply chain education (SCE) was also examined. Therefore, this study examined the relationship between work activities, knowledge sharing, SCE and sustainable social well-being. Population of the study is the garment companies of Indonesia. Employees of these companies were selected as the respondents. Consequently, data collection was performed among the garment companies of Indonesia. For the purpose of data collection, questionnaire was distribution among the garment company employees. Data were analyzed by using Partial Least Square (PLS). Results of the study highlighted that work activities have positive effect on sustainable social well-being. Knowledge sharing also shows the positive effect on sustainable social well-being. Moreover, SCE shows positive influence to enhance the sustainable social well-being directly and by playing the moderating role between work activities and sustainable social well-being.